Organization of Educational Environment at Pedagogical University: Concepts and Scenario of Changes - A. N. Makarenko; L. G. Smyshlyaeva; I. V. Volchkova; S. I. Pozdeeva; S. I. Semenova (Высшее образование в России)
The subjects of education satisfaction analysis with the teacher training results at the University was carried out. The training deficiencies and new challenges were identified, which made it possible to determine the guidelines for the development of pedagogical university. A variant to transform the organizational scheme of communications between university departments was presented to increase the efficiency of educational environment organization for professional training of future teachers.